Unblocking Oxygen Charge Compensation for Stabilized High‐Voltage Structure in P2‐Type Sodium‐Ion Cathode. Issue 16 (28th March 2022) - Zhu, He; Yao, Zhenpeng; Zhu, Hekang; Huang, Yalan; Zhang, Jian; Li, Cheng Chao; Wiaderek, Kamila M.; Ren, Yang; Sun, Cheng‐Jun; Zhou, Hua; Fan, Longlong; Chen, Yanan; et al.
Abstract: Layered transition‐metal (TM) oxides are ideal hosts for Li + charge carriers largely due to the occurrence of oxygen charge compensation that stabilizes the layered structure at high voltage. Hence, enabling charge compensation in sodium layered oxides is a fascinating task for extending the cycle life of sodium‐ion batteries. Herein a Ti/Mg co‐doping strategy for a model P2‐Na2/3 Ni1/3 Mn2/3 O2 cathode material is put forward to activate charge compensation through highly hybridized O2 p TM3 d covalent bonds. In this way, the interlayer OO electrostatic repulsion is weakened upon deeply charging, which strongly affects the systematic total energy that transforms the striking P2–O2 interlayer contraction into a moderate solid‐solution‐type evolution. Accordingly, the cycling stability of the codoped cathode material is improved superiorly over the pristine sample. This study starts a perspective way of optimizing the sodium layered cathodes by rational structural design coupling electrochemical reactions, which can be extended to widespread battery researches. Abstract : Here a Ti/Mg codoping strategy for a model P2‐Na2/3 Ni1/3 Mn2/3 O2 (NNM) cathode material is proposed to activate oxygen charge compensation at high voltage. In this way, the interlayer OO electrostatic repulsion is released, which modifies the P2–O2 transition into a moderate solid‐solution type evolution, and therefore remarkably enhances the cycling performance of the P2‐type NNM layered cathode.